Variability of running coordination in experts and novices: A 3D uncontrolled manifold analysis - Möhler, F.; Marahrens, S.; Ringhof, S.; Mikut, R.; Stein, T. (European Journal of Sport Science, 2020)
The uncontrolled manifold (UCM) approach has been widely used in recent studies to examine variability in daily tasks; however, it has not yet been used to study running or the effects of expertise. Therefore, the aim of this study was to analyse the synergy structure stabilizing the centre of mass (CoM) trajectory in experts compared to novices during running at two different speeds using a subject-specific 3D model. A total of 25 healthy young adults (13 experts, 12 novices) participated in the study. All subjects ran at 10 and 15 km h-1 on a treadmill. In each case, kinematics of 20 consecutive gait cycles were recorded and the effects of expertise and gait cycle phase on the synergy structure were investigated at both speeds. Specifically, the variance affecting the CoM (UCM?) , the variance not affecting the CoM (UCM?), and their ratio (UCMRatio) were analysed. Descriptively, in both groups there was a synergy stabilizing the CoM trajectory in running. However, the ANOVA showed no differences in UCMRatio between the two groups. In novices, UCM? and UCM? were significantly higher compared to experts at the 15 km h-1 condition. In both groups, there was more variability in the stance phase compared to the flight phase in the majority of cases. The results indicate that experts adopted a more consistent running style. The stride-to-stride variability was diminished but not abolished. This difference was only visible at the 15 km h-1 condition. Furthermore, variability was less constrained in the stance phase compared to the flight phase.